1999
DOI: 10.1037/0893-164x.13.2.78
|View full text |Cite
|
Sign up to set email alerts
|

Relations between posttraumatic stress symptom dimensions and substance dependence in a community-recruited sample of substance-abusing women.

Abstract: The factor structure of posttraumatic stress disorder (PTSD) symptoms, and correlations between PTSD dimensions and substance dependence, were examined in 295 substance-abusing women. Participants completed self-report measures of trauma exposure, PTSD symptoms, and alcohol dependence and underwent interviews regarding dependence on prescription anxiolytics and analgesics. Overall, PTSD symptoms were moderate in intensity, and 46% of the sample met criteria for PTSD diagnoses. A principal-components analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
95
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(110 citation statements)
references
References 43 publications
13
95
2
Order By: Relevance
“…Several studies have found PTSD increases risk of first onset of AUD in women Stewart et al, 1999) (Brady, Back, & Coffey, 2004;Stewart, 1996). Other studies have found AUD may increase risk of development of PTSD or be associated with a more severe and chronic course of symptoms (Acierno et al, 1999;Conrod & Stewart, 2003;Cottler et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have found PTSD increases risk of first onset of AUD in women Stewart et al, 1999) (Brady, Back, & Coffey, 2004;Stewart, 1996). Other studies have found AUD may increase risk of development of PTSD or be associated with a more severe and chronic course of symptoms (Acierno et al, 1999;Conrod & Stewart, 2003;Cottler et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…AUDs have been associated with more severe PTSD symptoms, such as elevated avoidance and hyperarousal symptoms (Back, Sonne, Killeen, Dansky, & Brady, 2003;Stewart, Conrod, Pihl, & Dongier, 1999) and more reexperiencing symptoms (Read, Brown, & Kahler, 2004).…”
mentioning
confidence: 99%
“…In most cases authors are permitted to post their version of the article (e.g. (Foa, Zinbarg, & Rothbaum, 1992), and may bear different functional relationships with interpersonal functioning, with physical health, and with symptoms often found co-morbid with post-traumatic stress symptoms (Kimerling, Clum, & Wolfe, 2000;Ruscio, Weathers, King, & King, 2002;Stewart, Conrod, Pihl, & Dongier, 1999;Stewart, Pihl, Conrod, & Dongier, 1998). Thus, a clear understanding of the nature of PTSD symptom clusters has the potential to inform both knowledge of how various PTSD symptoms develop and how these symptoms relate to co-occurring difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…Initial factor analyses of PTSD symptoms were exploratory in nature; direct testing of hypotheses regarding the nature of these symptoms is not possible with such analyses. To date, exploratory factor analyses of DSM-III-R/DSM-IV PTSD symptoms have been conducted with numerous populations, including survivors of fires, motor vehicle accidents and assaults, United Nations peacekeepers, refugees, and military veterans (Fawzi et al, 1997;Foa, Riggs, & Gershuny, 1995;Keane, 1993;Maes et al, 1998aMaes et al, , 1998bSack, Seeley, & Clarke, 1997;Shelby, Golden-Kreutz, & Andersen, 2005;Smith, Redd, DuHamel, Vickberg, & Ricketts, 1999;Smith, Perrin, Dyregrov, & Yule, 2003;Stewart et al, 1999;Taylor, Kuch, Koch, Crockett, & Passey, 1998). Two-, three-, four-, and five-factor solutions have been reported, with no solution clearly paralleling the symptom clusters suggested by the most recent versions of the DSM.…”
mentioning
confidence: 99%
“…It can also influence illness, either through changing health-related behaviour's such as smoking or via physiological pathways [8]. Studies thus far have found a positive relationship between stress and substance abuse [9], [10] with stress mostly resulting to substance abuse. Although, most literatures reviewed found a significant and positive correlation between stress and substance abuse, however, a few studies found no relationship between the constructs [11].…”
Section: Introductionmentioning
confidence: 99%